The Poetic Bliss of the Re-described Reality: Wallace Stevens: Poetry, Philosophy, and the Figurative Language - Hołda, Małgorzata (Text Matters: A Journal of Literature, Theory and Culture, 2020)
The article addresses the issue of the intimate but troublesome liaison between philosophy and literature—referred to in scholarship as “the ancient quarrel between poets and philosophers.” Its aim is double-fold. First, it traces the interweaving paths of philosophical and literary discourse on the example of Wallace Stevens’s oeuvre. It demonstrates that this great American modernist advocates a clear distinction between poetry and philosophy on the one hand, but draws on and dramatizes philosophical ideas in his poems on the other. The vexing character of his poetic works exemplifies the convoluted and inescapable connections between philosophy and poetry. Second, it discusses various approaches to metaphor, highlighting Stevens’s inimitable take on it. The diverse ways of tackling metaphorical language cognize metaphor’s re-descriptive and reconfiguring character. They embrace e.g., Stevens’s concept of metaphor as metamorphosis, or as “resemblance rather than imitation.” The to date interpretations of Stevens’s poetry in the light of a whole host of philosophies yield important insights into the meaningful interconnections between poetry and philosophy. However, rather than offering another interpretation of his poems from a given philosophical angle, the versatile voices presented here interrogate what poetry consists in.